Writing Strategies Used by English Department Students with Different Self-Esteem Level to Revise Their Essay(s) - Septemdira Intan Sari Suprobowati; Utari Praba Astuti; Ekaning Dewanti Laksmi (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: This qualitative study investigated writing strategies used by English Department students with different self-esteem level to revise their essay(s). This study involved 6 third-year students of English Language Teaching study program at Universitas Negeri Malang who have different self-esteem level (3 students with high self-esteem level and 3 students with moderate self-esteem level). There were three types of writing strategies that were used by the students with different self-esteem level to revise their essay(s), those were monitoring, getting feedback, and revising. Those strategies were considered helpful for the students to improve the quality of their essay(s). Abstrak: Penelitian kualitatif ini menginvestigasi strategi menulis yang digunakan oleh mahasiswa jurusan Bahasa Inggris dengan tingkat harga diri berbeda untuk merevisi esai mereka. Penelitian ini melibatkan enam siswa tahun ketiga program studi Pendidikan Bahasa Inggris di Universitas Negeri Malang yang memiliki tingkat harga diri berbeda (3 siswa dengan harga diri tinggi dan 3 siswa dengan harga diri sedang). Ada tiga jenis strategi menulis yang digunakan para siswa tersebut untuk merevisi esai mereka, yaitu monitoring, getting feedback, dan revising. Strategi menulis tersebut dianggap membantu para siswa untuk memperbaiki kualitas esai mereka.